Corporate Governance Country Assessment : El Salvador - World Bank (Washington, DC, 2014)
This report assesses El Salvador s corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in El Salvador. The OECD Principles focus on private-sector publicly traded companies, both financial and nonfinancial, but are also applicable to other public interest entities, including banks, insurance companies, and state-owned enterprises The equity market in El Salvador is small and has not showed much growth in the past five years. Most observers blame unwieldy approval processes for new share offerings, and the predominance in the economy of small- and medium-sized family-owned companies which do not have an interest in becoming public. Given the limited depth of the market, both regulator (SSF) and stock exchange (BVES) have taken measures towards regional integration. El Salvador today is participating in a regional initiative to develop an integrated Central American capital market with Panama and Costa Rica. Good corporate governance enhances investor trust, helps to protect minority shareholders, and can encourage better decision making and improved relations with employees, creditors, and other stakeholders. It is an important prerequisite for attracting the patient capital needed for sustained long-term economic growth.